Association of liver dysfunction with outcomes after cardiac surgery—a meta-analysis. (8th December 2022) - Kirov, Hristo; Caldonazo, Tulio; Audisio, Katia; Rahouma, Mohamed; Robinson, N Bryce; Cancelli, Gianmarco; Soletti, Giovanni J; Demetres, Michelle; Ibrahim, Mudathir; Faerber, Gloria; Gaudino, Mario; Doenst, Torsten
Abstract: OBJECTIVES: The aim of this study was to perform a meta-analysis of studies reporting outcomes in patients with liver dysfunction addressed by the model of end-stage liver disease and Child–Turcotte–Pugh scores undergoing cardiac surgery. METHODS: A systematic literature search was conducted to identify contemporary studies reporting short- and long-term outcomes in patients with liver dysfunction compared to patients with no or mild liver dysfunction undergoing cardiac surgery (stratified in high and low score group based on the study cut-offs). Primary outcome was perioperative mortality. Secondary outcomes were perioperative neurological events, prolonged ventilation, sepsis, bleeding and/or need for transfusion, acute kidney injury and long-term mortality. RESULTS: A total of 33 studies with 48 891 patients were included. Compared with the low score group, being in the high score group was associated with significantly higher risk of perioperative mortality [odds ratio (OR) 3.72, 95% confidence interval (CI) 2.75–5.03, P < 0.001]. High score group was also associated with a significantly higher rate of perioperative neurological events (OR 1.49, 95% CI 1.30–1.71, P < 0.001), prolonged ventilation (OR 2.45, 95% CI 1.94–3.09, P < 0.001), sepsis (OR 3.88, 95% CI 2.07–7.26, P < 0.001), bleeding and/or need for transfusion (OR 1.95, 95% CI 1.43–2.64, P < 0.001), acute kidney injury (OR 3.84, 95% CI 2.12–6.98, P < 0.001) and long-term mortality (incidence risk ratio 1.29, 95% CI 1.14–1.46, P < 0.001) CONCLUSIONS: The analysis suggests that liver dysfunction in patients undergoing cardiac surgery is independently associated with higher risk of short and long-term mortality and also with an increased occurrence of various perioperative adverse events. Abstract : The evaluation of various preoperative risk factors and their association with surgical outcome has become an important aspect of clinical decision-making.